Synthesis and Antisecretory Activity of 6-Substituted 5-Cyanomethylimidazo[2,1-b]-thiazoles and 2,6-Dimethyl-5-hydroxymethylimidazo[2,1-b][1,3,4]thiadiazole - Andreani, Aldo; Leoni, Alberto; Locateur, Alessandra; Morigi, Rita; Rambaldi, Mirella; Simon, Wolfgang A; Senn-Bilfinger, Jörg (Arzneimittelforschung, 2000)
The synthesis of imidazo[2,1-b]thiazole and imidazo[2,l-b][l,3,4]thiadiazole derivatives, related to known antiulcer agents, is reported. 5-Cyanomethyl-6-methylimidazo[2,l-b]thiazole showed significant antisecretory activity in the isolated rabbit gastric glands assay.
Keywords: Antiulcer drugs; Imidazothiadiazoles, antisecretory activity, synthesis; Imidazothiazole, antisecretory activity, synthesis